Meningkatkan Kemampuan Representasi Matematis Siswa Kelas X.7 SMAN 7 Pekanbaru Melalui Implementasi Model Problem Based Learning - Rotua, Yuli Ani; Sakur, Sakur; Saragih, Sehatta (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aimed to improve students’ mathematical representation ability through the Problem Based Learning (PBL) model on the topic of linear equations and inequalities in phase E. The subjects were students of class X.7 at SMA Negeri 7 Pekanbaru in the 2024/2025 academic year. The research employed Classroom Action Research (CAR), which was conducted in two cycles, each consisting of two meetings through the stages of planning, implementing actions, observing, and reflecting. The research instruments consisted of learning tools (ATP and teaching module) and data collection instruments in the form of observation sheets for teacher and student activities, as well as a mathematical representation test (MRT).The results showed that the application of the PBL model improved both the learning process and students’ mathematical representation ability. The analysis of test results indicated significant improvement: the number of students in the very low category decreased from 29 to 3, while those in the high category increased from 2 to 12, and in the very high category from 0 to 11. Thus, the implementation of the PBL model proved effective in improving the learning process and enhancing students’ mathematical representation ability in linear equations and inequalities